Databook of rheological additives - Wypych, Anna; Wypych, George (ChemTec Publishing, 2022)
"Rheological additives are of interest to many industries, including paints, coatings, cosmetics, mortars, cementitious products, various polymer processing methods, sealants, inks, greases, drilling, food products, to name some of the most important. Their selection and applications change and require frequent updates. The Databook of Rheological Additives is frequently used in combination with the Handbook of Rheological Additives. Both books do not overlap but complement each other, providing together comprehensive information on rheological additives."--